Design of a simplified cranial substitute with a modal behavior close to that of a human skull - Elster, Natacha; Boutillier, Johanna; Bourdet, Nicolas; Magnan, Pascal; Naz, Pierre; Willinger, Rémy; Deck, Caroline (Frontiers in Bioengineering and Biotechnology, 2024)
Individuals exposed to the propagation of shock waves generated by the detonation of explosive charges may suffer Traumatic Brain Injury. The mechanism of cranial deflection is one of many hypotheses that could explain the observed brain damage. To investigate this physical phenomenon in a reproducible manner, a new simplified cranial substitute was designed with a mechanical response close to that of a human skull when subjected to this type of loading. As a first step, a Finite Element Model was employed to dimension the new substitute. The objective was indeed to obtain a vibratory behavior close to that of a dry human skull over a wide range of frequencies up to 10 kHz. As a second step, the Finite Element Model was used together with Experimental Modal Analyses to identify the vibration modes of the substitute. A shaker excited the structure via a metal rod, while a laser vibrometer recorded the induced vibrations at defined measurement points. The results showed that despite differences in material properties and geometry, the newly developed substitute has 10/13 natural frequencies in common with those of dry human skulls. When filled with a simulant of cerebral matter, it could therefore be used in future studies as an approximation to assess the mechanical response of a simplified skull substitute to a blast threat.